2016
DOI: 10.1093/brain/aww014
|View full text |Cite
|
Sign up to set email alerts
|

CCDC88A mutations cause PEHO-like syndrome in humans and mouse

Abstract: P rogressive E ncephalopathy with oedema, H ypsarrhythmia and O ptic atrophy (PEHO) is a rare, neurodegenerative disorder of unknown aetiology. Nahorski et al . identify the first causative recessive mutation in CCDC88A , which encodes the actin-binding protein Girdin. The phenotype and brain anatomy of the Ccdc88a knockout mouse resemble those of human PEHO syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Since the original clinical description of this condition in 1991, a number of different genes and modes of inheritance have been associated with clinical presentations said to be consistent with PEHO, or thought to be PEHO-like in nature, including de novo dominant variants in CDKL5 and KIF1A and biallelic mutations in CCDC8A (Gawlinski et al , 2016; Langlois et al , 2016; Nahorski et al , 2016) . The phenotype in the Italian family, as well as consistent overlapping clinical aspects present in the other families described here, provides cause to consider that PRUNE1 should now also be added to the list of genes in which mutations may present in children with epileptic encephalopathy and PEHO-like features.…”
Section: Discussionmentioning
confidence: 99%
“…Since the original clinical description of this condition in 1991, a number of different genes and modes of inheritance have been associated with clinical presentations said to be consistent with PEHO, or thought to be PEHO-like in nature, including de novo dominant variants in CDKL5 and KIF1A and biallelic mutations in CCDC8A (Gawlinski et al , 2016; Langlois et al , 2016; Nahorski et al , 2016) . The phenotype in the Italian family, as well as consistent overlapping clinical aspects present in the other families described here, provides cause to consider that PRUNE1 should now also be added to the list of genes in which mutations may present in children with epileptic encephalopathy and PEHO-like features.…”
Section: Discussionmentioning
confidence: 99%
“…Within a consanguineous family, two siblings and a cousin had a PEHO-like condition, which we have previously described 31. The affected children had a homozygous, and the parents the heterozygous variant, c.2313delT, p.Leu772*ter in the gene CCDC88A.…”
Section: Resultsmentioning
confidence: 94%
“…The ThiF domain of UBA5 is shown as a white box. See Nahorski et al 31 for family tree for family C and illustration of CCDC88A variants. Family tree for family A and variants in the PCLO gene and its protein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their roles in brain development have not been fully explored, but Girdin can promote long-range neuronal migration by affecting cell adhesion and, separately, can affect synaptic plasticity (Enomoto et al, 2009;Wang et al, 2011;Nakai et al, 2014;Itoh et al, 2016). Loss of Girdin/CCDC88A causes PEHO syndrome, characterized by progressive encephalopathy and optic atrophy (Nahorski et al, 2016). Intriguingly, loss of CCDC88C leads to congenital hydrocephalus similar to that seen in loss of L1CAM/SAX-7 (Ekici et al, 2010;Drielsma et al, 2012;Ruggeri et al, 2018), although no relationship between CCDC88C and L1CAM has been identified previously.…”
Section: Grdn-1mentioning
confidence: 99%